[Yerusholaim de'-Liṭa : di Yidishe ḳulṭur in der Liṭe] = Jerusalem of Lithuania : a reader in Yiddish cultural history - Frakes, Jerold C. (Ohio State University Press, 2011)
This is a Yiddish reader for intermediate-level students. It contains historical readings that recreate the importance of Vilnius (Lithuania) in preserving Jewish theology and culture during the last five centuries.